Desain Mini Boiler Pipa Api Jenis Scotch Menggunakan Bahan Bakar Batu Bara Dengan Pendekatan Kajian Teoritis - Muhammad Helmi Kurniawan; Khusnul Khotimah Ayuningtiyas (Jurnal Mekanik Terapan, 2022)
A boiler is an energy conversion device that can convert water into usable steam by regulating the pressure and temperature of the steam. A steam boiler (boiler) is a steam component used as an energy source in processes in the food industry or other industries, due to its important role in manufacturing. In this research, we examined based on the investigation of the existing data. The figures obtained are obtained from appropriate publications and processed to analyze the data from the search results. From experimental analysis, water vapor theorem results are obtained for liquid water. kettle diameter 150 cm; kettle length 300 cm; fire pipe diameter 60 cm. The research obtained is expected to serve as a model for mechanical design models that can be used in industry, training centers and educational institutions.